Språk, tekst og medvit - Haugen, Tor Arne; Myklebost, Svenn-Arve; Brunstad, Endre; Helset, Stig Jarle (Skriftkultur, 2021)
This volume of Skriftkultur illustrates how the cross-disciplinary field of writing culture can provide new perspectives on fundamental questions. A definitive foundation of all research and scholarly activity is that it is based in writing. This is true not only within the humanities, but in all scientific disciplines. Scientific theories and modes of thought are linguistic constructions within cultural communities, and science happens in written form. Basic issues in exploring language and writing are thus also basic issues in other written language practices, whether they are scientific or more general. The relationship between a language, texts the language is the basis of, and awareness of the language users is precisely about such basic issues. What are our grounds for understanding, describing and explaining these situations, and to what extent do different subjects and disciplines provide different approaches and answers to such questions?